The Development of Inquiry Science Worksheet to Facilitate the Process Skills - Margaretha Ordo Servitri; Wulan Trisnawaty (Journal of Education and Learning (EduLearn), 2018)
This research aimed for developing Inquiry Worksheet to facilitate the process skill. Inquiry Worksheet gave the opportunity for student to make good observations in giving hypothesis, designing the experiment, collecting, analyzing, and inferring the data. To involve the students in Inquiry process is the important point in Science lessons which can help the students to develop Science literacy and give the opportunity to drill their Science process skill. This research used the steps of developing 4P but the fourth step was not used, this analysis used the descriptive qualitative. Based on the validation result showed the Lesson Plan (RPP) and Inquiry Worksheet (LKS) had been developed were in valid category. The implementation of the good Lesson Plan for Evaluation Results was classically achieved. The process skill obtained 100 for the average score. For pretest and posttest, the students obtained 82.85 and 57.14. Learning using the Inquiry worksheet showed good responses by the students. The conclusion of this research was Inquiry Worksheet competent to facilitate the process skills.